2013
DOI: 10.5603/fm.2013.0027
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the abductor pollicis longus tendon: an anatomic study

Abstract: (Folia Morphol 2013; 72, 2: 161-166)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
(25 reference statements)
4
17
1
Order By: Relevance
“…Different types of accessory band insertions have been described in the literature [2][3][4][5][6][7][8][9][10]13], and such great morphological variability is believed to have an embryological basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of accessory band insertions have been described in the literature [2][3][4][5][6][7][8][9][10]13], and such great morphological variability is believed to have an embryological basis.…”
Section: Discussionmentioning
confidence: 99%
“…The APL demonstrates a high degree of variability with regard to the number of its accessory bands and their insertion [2][3][4][5][6][7][8][9][10]. The presence of multiple tendons originating from the APL is clinically relevant, as it can lead to the development of de Quervain's syndrome, which is caused by stenosing tenosynovitis.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have studied the variation of APL tendon. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 39 40 41 42 43 44 45 46 47 48 49 But only few reports are available from the Indian subcontinent. 9 14 30 31 46 47 48 49 There seems to be an ethnical variation in the origin, insertion, and arrangement of these tendons.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Multiple tendinous insertion of APL has been reported by many authors. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 The anatomical variation may remain asymptomatic or may present with painful conditions like de Quervain tenosynovitis (DQT). 2 5 6 19 The treatment of such condition in severe cases involves either an injection therapy or surgical decompression of the first extensor compartment.…”
Section: Introductionmentioning
confidence: 99%
“…They noted the apl to have 2-6 tendons of which the double tendon was found to be the most common i.e. In 40% of the cases [13]. Roy et al and tewari et al in their respective studies from the indian subcontinent also reported the bi-tendinous slips of apl as the most common pattern of apl arrangement on dorsum of the wrist [14,15].…”
Section: Methodsmentioning
confidence: 99%